INVESTIGATION OF ENERGY, EXERGY, AND EMISSION PERFORMANCE OF TURBULATORS INSERTS HEAT EXCHANGER WITH TERNARY HYBRID NANOFLUID COOLANT - Rai R.; Kumar V.; Sahoo R.R. (My University, 2025)
The improvement of technologies necessitates using a meticulous heat dissipation method to enhance the exergy efficiency of small air heat exchangers. To improve thermal performance, plain tube (PT) heat exchangers (HX) use passive inserts, such as dimpled twisted turbulator inserts (DTTI) and twisted turbulator inserts (TTI) filled with a ternary hybrid nanofluid (THNF) based on water. Energy, exergy use, and environmental impacts in the future are the primary foci of the inquiry on THNF replacement inserts. Using water as the operating fluid, copper oxide (CuO), aluminum oxide (Al2O3), and titanium oxide (TiO2) nanoparticles are dissolved. The resultant THNF is injected at 0.06%, 0.09%, and 0.12%. Energy, exergy, and emissions are used to study certain features of control fluid flow. The results of the experiments show that using TTI and DTTI along with THNF makes a small air heat exchanger much more efficient at heating and cooling. When DTTI and TTI turbulator plugs are used in regular tubes with THNF of 0.12% (v/v) concentration, friction factor, heat transfer, reversibility, and exergy change all get much better. When DTTI or TTI turbulator plugs are put into the core of the tube, the carbon dioxide (CO2) release goes up by 2.6 to 2.1. People who use DTTI with THNF of 0.12% (v/v) concentration as the operating fluid and a tube plug will get performance evaluation criterion (PEC) numbers between 1.076 and 1.04. A careful study of friction factor, heat transfer, exergy efficiency increase, and environmental effect shows that DTTI is a superior passive device for enhancing heat transfer efficiency, particularly when combined with THNF of 0.12% (v/v) concentration. © 2024 by Begell House, Inc. www.begellhouse.com.